“New Vision” Today - BlyuherYulia Nikolaevna (Communications. Media. Design, 2022)
This article observes the appearance of the new compositional techniques in the field of modern illustration, comics, and other areas of visual arts, due to the technical and software progress, its influence on the formation of visual patterns and principles of consolidation in mass culture. This is the attempt to classify such a kind of techniques in modern visual culture based on ideas of L. Mohoy-Nagy and research the forming figurative systems principles and visual codes as ways of representing a certain sensual experience.